La Dematerialisation : Determinant Primordial De L’efficacite De La Commande Publique - El Amry, Abdelkader (European Scientific Journal, ESJ, 2018)
In Morocco, public procurement represents 17.4% of GDP, equivalent to 195 billion dirhams in 2018 (Maghreb Arab Press, 2018), which makes it more exposed to unhealthy practices that can be engaged both by officials and operators across all stages of the procurement process. Above all, such practices create a climate devoid of transparency and generates weaknesses in public procurement systems. It is, therefore, essential for the Moroccan administration to integrate anti-corruption measures into the procurement process. Among these anti-corruption measures, there is the " e-procurement " which all specialists in the field of public control unanimously assume that it has become key in the promotion of competition, transparency, integrity, simplification of procedures, and modernization of public expenditure execution processes. Moreover, they admit that it contributes to a large extent to reduce corruption without destroying it. To inquire about the veracity of the contribution of the e-procurement to the efficiency of public order, a questionaire was administered to four co-ordinators and four companies of different working fields in the city of Meknes. The objective is to explore the relationship between e-procurement and the fundamental principles of public control. Eventually, the results of this study revealed that eprocurement is determinant to the effectiveness of public procurement.